Analisis Common Size Pada Pt Unilever Tbk, Pada Priode 2019-2021 Sebagai Indikator Untuk Mengukur Kinerja Keuangan - Nasution, Hermansyah; Megawati, Liya (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the financial performance of PT. Unilever Indonesia Tbk, using the Common Size method in the 2019-2021 period. The Common Size method is used to compare changes in the proportion of each item in the financial statements during the period studied, thus providing a clearer picture of the company's financial structure and performance. This research uses financial data taken from the annual financial statements of PT Unilever Indonesia Tbk during the 2019-2021 period. Common Size analysis is carried out by descriptive analysis methods with a quantitative approach to determine company performance. This research method is used to analyze data by describing or describing the data that has been collected objectively, so as to provide a clear picture of the financial performance of Unilever Indonesia Tbk. Priode 2019 - 2021 in the form of percentage numbers from the account contained in the balance sheet and income statement using common size analysis. This type of quantitative data is used in processing information in the form of numbers in financial statements into percentages of total assets.